Postfeminisms : feminism, cultural theory, and cultural forms - Brooks, Ann, 1952- (Routledge, 1997)
This book examines how feminism is being redefined for the twenty-first century. Concepts covered include: feminist epistemology, Foucault, psychoanalytic theory and semiology, cultural politics and sexuality and identity.